WAYS TO SOLVE POVERTY PROBLEMS IN THE REPUBLIC OF UZBEKISTAN - G.Kh.Utemuratova; U.K. Kulmuratova (Scholar Express Journals, 2025)
This article examines the poverty eradication model in Uzbekistan, focusing on the strategies and measures taken by the government to combat this socio-economic challenge. After gaining independence in 1991, Uzbekistan faced many challenges related to poverty and inequality. In response to these challenges, a comprehensive program was developed to improve the living conditions of the population and create a sustainable economy
Keywords: social support; development programs; overty reduction strategies